COMMUNICATIVE APPROACH IN TEACHING ENGLISH FOR 3RD YEAR ENGLISH DEPARTMENT STUDENTS: ADVANTAGES AND WEAKNESSES - Ike Revita (Universitas Katolik Indonesia Atma Jaya, 2015)
English as international language is learned by many people allover the world. In certain country, like Indonesia, English is stillregarded as foreign language different from in Philippine orMalaysia in which English is their second language. Thesedifferent positions make the emergence of various ways ofteaching English. This writing is aimed at describing one way ofteaching English called communicative approach. The object ofthis writing is to see the advantages and weaknesses of thismethod applied for the beginners. The research is conducted atEnglish Department Andalas University where third yearstudents become the subject. Data are collected by observationalmethod with note-taking and interviewing technique. Theanalysis is done by using referential identity method related tothe concept proposed by Savignon (2002). The result of analysisis descriptively presented. Having analyzed data, it is found threeadvantages and three weaknesses of using communicativeapproach in teaching English for 3rd year English Departmentstudents. The advantages are (1) enhancing students’ competencein speaking English in various situation; (2) encouraging studentsto practice their English in real communication; (3) stimulatingthe students to speak communicatively; (4) motivating studentsto be brave interacting using English. The weaknesses are (1)focusing much on meaning not form; (2) regarding learningstructure is useless and irrelevant; and (3) discouraging studentswho have lack vocabularies to speak.Keywords: Communicative Approach, English as anInternational language, English communication